Effects of early life arsenic exposure on the respiratory system, blood pressure and renal function in children and adolescents in rural Bangladesh, Matlab : a thesis presented in partial fulfillment of the requirements for the degree of PhD in Public Health (Epidemiology), Massey University, Wellington, New Zealand - Khan, Md Alfazal (Massey University, 2016)
Abstract not supplied
Keywords: Arsentic; Toxicology; Pediatric toxicology; Environmentally induced diseases; Epidemiology; Bangladesh